2013
DOI: 10.3389/fpubh.2013.00060
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Juvenile Firesetting: Results from Two National Survey Datasets

Abstract: The main purpose of this study was to address gaps in existing research by examining the relationship between academic performance and attention problems with juvenile firesetting. Two datasets from the Achenbach System for Empirically Based Assessment (ASEBA) were used. The Factor Analysis Dataset (N = 975) was utilized and results indicated that adolescents who report lower academic performance are more likely to set fires. Additionally, adolescents who report a poor attitude toward school are even more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Intentional firesetting represents one of the most complex and costly antisocial behaviors engaged in by a significant minority of young people. Although estimates vary, community studies indicate that firesetting occurs in between 5% and 38% of children and adolescents (Bowling, Merrick, & Omar, 2014; Chen, Arria, & Anthony, 2003; Dadds & Fraser, 2006; Del Bove, Caprara, Pastorelli, & Paciello, 2008; MacKay, Paglia-Boak, Henderson, Marton, & Adlaf, 2009; Martin, Bergen, Richardson, Roeger, & Allison, 2004; Watt, Geritz, Hasan, Harden, & Doley, 2015). Prevalence rates in clinical populations have been reported to be substantially higher, with between 46% and 67% of young people in inpatient and offending samples reporting a history of firesetting (Kolko, Day, Bridge, & Kazdin, 2001; Watt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intentional firesetting represents one of the most complex and costly antisocial behaviors engaged in by a significant minority of young people. Although estimates vary, community studies indicate that firesetting occurs in between 5% and 38% of children and adolescents (Bowling, Merrick, & Omar, 2014; Chen, Arria, & Anthony, 2003; Dadds & Fraser, 2006; Del Bove, Caprara, Pastorelli, & Paciello, 2008; MacKay, Paglia-Boak, Henderson, Marton, & Adlaf, 2009; Martin, Bergen, Richardson, Roeger, & Allison, 2004; Watt, Geritz, Hasan, Harden, & Doley, 2015). Prevalence rates in clinical populations have been reported to be substantially higher, with between 46% and 67% of young people in inpatient and offending samples reporting a history of firesetting (Kolko, Day, Bridge, & Kazdin, 2001; Watt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Deliberate firesetting by young people is increasingly conceptualized as occurring within the context of antisocial behavior. Firesetting is a diagnostic criterion of conduct disorder (American Psychiatric Association, 2013), and many risk factors for firesetting behavior, such as family dysfunction, abuse history, impulsivity, and poor school performance, are common to conduct problems (Bowling et al, 2014; Hoerold & Tranah, 2014; Lambie & Randell, 2011; Murray & Farrington, 2010; Walsh & Lambie, 2013). A recent study reported that youth offenders were nearly three and a half times more likely to have engaged in firesetting than young people in the community (Watt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among psychiatric samples, the incidence of fire setting has ranged from 2.3% to 15% for outpatients and 14.3% to 34.7% for inpatients (Del Bove et al, 2008; Kolko & Kazdin, 1988; MacKay et al, 2009). Among community samples, rates among children ages 4–8 years are as low as 5% (Dadds & Fraser, 2006), with about 4.5% of adolescents found to engage in fire setting (Howell Bowling et al, 2013). Further complicating the problem are the high rates of repeat fire behavior among youth, with up to 59% reengaging in fire involvement (Kolko et al, 2001; Kolko & Kazdin, 1992; MacKay et al, 2006).…”
Section: Fire Behavior In Children and Adolescents: Selected Correlat...mentioning
confidence: 99%
“…For emotional and behavioral regulation (internalizing distress, impulse, and attentional control) in combination with fire interest, the regulation of emotions such as anger and internalizing distress have been implicated in the fire behavior of children and adolescents (Del Bove et al, 2008; Howell Bowling et al, 2013; Kolko & Kazdin, 1991). Children self-identified as highly curious about fire (including “interest” and “excitement”) may be more emotionally dysregulated and more involved with fire.…”
Section: Correlates and Risk Factors In Problematic Fire Behavior At ...mentioning
confidence: 99%